EFFECTS OF CASTRATION, DEHORNING, AND DOCKING ON GROWTH PERFORMANCE AND FEED INTAKE OF YANKASA LAMB - Mundi, Harrat . L.; Sani, Umar M.; Yusuf, Zikrullah Z.; Dogara, Umar M.; Mundi, Ismaila; Abdullahi, Zainab (FUDMA Journal of Sciences, 2026)
This study aimed to investigate the effects of castration, dehorning, and docking on the growth performance and feed intake of Yankasa lambs. A total of twelve (12) three-month-old male lambs were used for this study. The lambs were sourced from a reputable farm in Lafia, Nasarawa State. The animals were tagged and allowed to acclimatize for four weeks prior to the commencement of the experiment. The lambs were grouped into six treatment groups as follows: Control, castrated, dehorned, dehorned and docked, docked and castrated, and docked, dehorned, and castrated. The procedures were carried out based on established humane veterinary standards. Data were analyzed using analysis of variance (ANOVA) with SAS software. All the lambs had an average initial weight of 14,075 ± 75.0 g. The group that was docked, dehorned, and castrated had the highest final weight (21,650 ± 650 g) and total weight gain (7,525 ± 275 g), followed by the control group. However, the differences were not statistically significant (P > 0.05). Daily and weekly weight gains also did not differ significantly among the treatment groups. There was no statistically significant difference in daily feed intake, although the docked and castrated group (766.67 ± 66.6 g) and the docked, dehorned, and castrated group (766.67 ± 42.1 g) consumed slightly less feed compared to the other groups.